Efficacy of a Feed Dispenser for Horses in Decreasing Cribbing Behaviour - Silvia Mazzola; Clara Palestrini; Simona Cannas; Eleonora Fè; Gaia Lisa Bagnato; Daniele Vigo; Diane Frank; Michela Minero (Veterinary Medicine International)
Cribbing is an oral stereotypy, tends to develop in captive animals as a means to cope with stress, and may be indicative of reduced welfare. Highly energetic diets ingested in a short time are one of the most relevant risk factors for the development of cribbing. The aim of this study was to verify whether feeding cribbing horses through a dispenser that delivers small quantities of concentrate when activated by the animal decreases cribbing behaviour, modifies feeding behaviour, or induces frustration. Ten horses (mean age 14 y), balanced for sex, breed, and size (mean height 162 cm), were divided into two groups of 5 horses each: Cribbing and Control. Animals were trained to use the dispenser and videorecorded continuously for 15 consecutive days from 1 h prior to feeding to 2 h after feeding in order to measure their behaviours. The feed dispenser, Quaryka®, induced an increase in time necessary to finish the ration in both groups of horses (P<0.05). With Quaryka, cribbers showed a significant reduction of time spent cribbing (P<0.05). After removal of the feed dispenser (Post-Quaryka), cribbing behaviour significantly increased. The use of Quaryka may be particularly beneficial in horses fed high-energy diets and ingesting the food too quickly.